Respiratory syncytial virus burden in children under 2 years old in understudied areas worldwide: gap analysis of available evidence, 2012–2022 - Sini de Almeida, Rodrigo; Leite, João; Atwell, Jessica E.; Elsobky, Malak; LaRotta, Jorge; Mousa, Mostafa; Thakkar, Karan; Fletcher, Mark A. (Frontiers in Pediatrics, 2024)
Background We evaluated published evidence (2012–2022) on pediatric RSV burden in 149 countries within World Health Organization (WHO) regions of Africa (AFRO), Americas (AMRO, excluding Canada and the USA), Eastern Mediterranean (EMRO), Europe (EURO, excluding European Union countries and the UK), Southeast Asia (SEARO), and Western Pacific (WPRO, excluding Australia, China, Japan, New Zealand, and South Korea). Methods Gap analysis on RSV-associated disease (hospitalizations, hospital course, mortality or case fatality, detection, and incidence) in children ≤2 years old, where hospitalization rates, hospital course, mortality rate, case fatality rate (CFR), and postmortem detection rates were summarized, by region, for each country. Results Forty-two publications were identified covering 19% of included countries in AFRO, 18% in AMRO, 14% in EMRO, 15% in EURO, 18% in SEARO, and 13% in WPRO. Methods, case definitions, and age groups varied widely across studies. Of these 42 publications, 25 countries reported hospitalization rate, hospital course, mortality rate, CFR, and/or postmortem detection rate. RSV hospitalization rate (per 1,000 children per year/child-years) was higher among ≤3-month-olds (range, 38 in Nicaragua to 138 in the Philippines) and ≤6-month-olds (range, 2.6 in Singapore to 70 in South Africa) than in 1–2-year-olds (from 0.7 in Guatemala to 19 in Nicaragua). Based on 11 studies, in AFRO (South Africa), AMRO (Chile and Mexico), EMRO (Lebanon and Jordan), EURO (Israel and Turkey), and SEARO (India), hospitalized children ≤2 years old remained hospitalized for 3–8 days, with 9%–30% requiring intensive care and 4%–26% needing mechanical ventilation. Based on a study in India, community-based CFR was considerably higher than that in the hospital (9.1% vs. 0% in ≤3-month-olds; 7.1% vs. 2.8% in ≤6-month-olds). Conclusions National and regional heterogeneity of evidence limits estimates of RSV burden in ≤2-year-olds in many WHO region countries, where further country-specific epidemiology is needed to guide prioritization, implementation, and impact assessment of RSV prevention strategies.